REMODELLING OF MORPHOLOGICAL AND FUNCTIONAL PARAMETERS OF THE GUMS AND ELEMENTS OF THE HAEMOMICROCIRCULATORY BED UNDER THE INFLUENCE OF FOOD ADDITIVES COMPLEX - Bilash, S.M.; Oleksiienko, V.V.; Pronina, O.M.; Koptev, M.M.; Pirog-Zakaznikova, A.V.; Donchenko, S.V.; Mamai, O.V. (World of Medicine and Biology, 2024)
Nowadays, food additives are widespread in the food industry. This is not only due to the fact that they greatly improve the taste of products but also because they allow products to be stored for a longer period of time. Unfortunately, they have many negative properties that manifest themselves only after a certain period of time. The experiment aimed to identify the effects of various food additives on the gums and changes in their composition. The study found that the impact of a complex of food additives (monosodium glutamate, sodium nitrite and Ponceau 4R) on the microvasculature of the gums of rats causes a violation of haemodynamic conditions, and over time a violation of the blood supply to the gums. Morphological changes of microvessels are observed mainly from the fourth week of the experiment and are characterised by vasodilation or vasoconstriction, the formation of erythrocyte aggregates, which leads to significant pathological changes in the structural organisation of the gums and blood supply to the gums as an integral organ of the oral cavity.